(untitled) (Comprehensive Journal of Science, 2025)
Background: Acute Flaccid Paralysis (AFP) surveillance represents a fundamental component of global poliomyelitis eradication strategies. In Libya, a nationwide AFP surveillance system has been operational for several decades, serving as a key mechanism for detecting poliovirus circulation and assessing surveillance performance indicators. Objective: This study aimed to analyze long-term trends in AFP reporting, Non-Polio AFP (NP-AFP) rates, Non-Polio Enterovirus (NPEV) detection, Sabin-like (SL) virus isolation, and the geographical distribution of AFP cases in Libya between 1998 and 2023. Methods: A retrospective descriptive analysis was conducted using national AFP surveillance data obtained from weekly epidemiological reports up to week 52 of 2023. Annual reporting trends, virological indicators, and regional case distributions were examined using descriptive statistical methods. Results: AFP reporting demonstrated a progressive increase over the study period, with pronounced peaks observed in 2018, 2019, 2020, 2022, and 2023. Benghazi, Al-Jabal Al-Akhdar, and Tripoli consistently reported the highest number of cases in recent years. The NP-AFP rate exceeded the World Health Organization (WHO) benchmark of ≥2 per 100,000 children under 15 years throughout the study period, reaching its highest levels after 2018. NPEV detection peaked at 16% in 2013, while SL virus isolation showed notable peaks in 2003, 2005, 2009, 2018, and 2020. In 2023, a total of 115 AFP cases were reported, including 113 Libyan and 2 non-Libyan children. Conclusion: Libya maintains a high-quality AFP surveillance system with performance indicators consistently exceeding WHO standards. Continued investment in laboratory capacity and targeted surveillance strengthening in southern regions are essential to sustain polio-free status and enhance early enterovirus detection.